MicroRNA-21-5p targets PDCD4 to modulate apoptosis and inflammatory response to Clostridium perfringens beta2 toxin infection in IPEC-J2 cells. (January 2021) - Gao, Xiaoli; Huang, Xiaoyu; Yang, Qiaoli; Zhang, Shengwei; Yan, Zunqiang; Luo, Ruirui; Wang, Pengfei; Wang, Wei; Xie, Kaihui; Gun, Shuangbao
Abstract: Clostridium perfringens ( C. perfringens ), a toxin-producing enteric pathogen, causes a variety of intestinal infections in humans and animals. C. perfringens beta2 (CPB2) toxin has been considered to be a strong virulence factor for C. perfringens infectious enteric diseases (CPED). Altered levels and functions of microRNA-21-5p (miR-21-5p) have been associated with apoptosis and inflammation response in pathological processes. However, little is known about its functional mechanism in CPED. Here, we found that miR-21-5p expressed in multiple tissues of pig, had a highest level in jejunum, and significantly upregulated in intestinal porcine epithelial cells (IPEC-J2) exposed to CPB2 toxin. Noteworthily, transfection of CPB2-treated IPEC-J2 cells with miR-21-5p mimic increased cell viability and Bcl2 expression, as well as reduced cytotoxicity, apoptosis rates and Bax level. Moreover, overexpression of miR-21-5p significantly suppressed the levels of interleukin (IL)-6, IL-8, TNF-α, IL-1β and nuclear factor-kappa B (NF-κB p65) activity induced by CPB2 toxin, whereas that of the IL-10 was increased in IPEC-J2 cells. On the contrary, transfection of miR-21-5p inhibitor promoted CPB2-induced cell apoptosis and inflammation. Furthermore, we validated that programmed cell death 4 (PDCD4) was strikingly downregulated in CPB2-treated IPEC-J2 cells. PDCD4 exhibited opposing effects to those of miR-21-5p mimic on IPEC-J2 cells, and restoration of PDCD4 expression counteracted the suppressive effect of miR-21-5p on CPB2-induced apoptosis and inflammatory response. Collectively, our findings demonstrated that miR-21-5p was involved in regulating the immune response triggered by CPB2 toxin and contributed to protective effects in CPB2-induced CPED cell model by targeting PDCD4 . Highlights: miR-21-5p expression was elevated in IPEC-J2 cells after CPB2 toxin infection. miR-21-5p suppressed CPB2-induced apoptosis and inflammation in IPEC-J2 cells. PDCD4 was a direct target of miR-21-5p in IPEC-J2 cells.